Legal aspects of public interest participation in environmental management and conservation - Truter, Jan Daniel De Villiers (Centre for Law and Society, 2026)
The plethora of reporting on environmental issues in newspapers, news broadcasts on radio and television and in many other areas of daily life has created a new awareness of the environment in the general public. The cultivation of this awareness heightens the public's interest in becoming involved in environmental matters. Although individuals often realise that some action is required to address an environmental problem, they are in general ignorant of how environmental law can be applied to the issue. Even amongst informed environmentalists there is no common procedure for approaching environmental issues. Public interest participation in managing and conserving the environment is one avenue open to the public